Perilaku Pembelian Pestisida Petani Padi di Kecamatan Kanor Kabupaten Bojonegoro - Sari, Betty Nur Indah; Setiawan, Budi; Riana, Fitria Dina (Jurnal Ilmiah Global Education, 2024)
The use of pesticides to eradicate plant pest organisms (OPT) faced by rice farmers in Kanor District is an effective solution to reduce the threat of crop failure which has the potential for losses. However, the use of pesticides without control and non-compliance with usage rules carries a risk of damaging rice fields. The behavior of rice farmers in using pesticides is confirmed to have low compliance, including the habit of mixing two or more different brands, as well as using higher doses. The behavior of pesticide purchasing decisions made by farmers in this research will be tested through a marketing mix consisting of product quality, price, place and promotions carried out by pesticide producers. This research is a quantitative research, taking research samples from rice farmers in Kanor District, which is a productive rice producing center in Bojonegoro Regency. Research data analysis uses descriptive statistics and structural equation modeling (SEM) analysis using the smartPLS application. The research results found several findings, including the behavior of farmers in using pesticides, 73.1 percent mixing various brands, 20.4 percent using higher doses. The most common reason farmers choose a brand of pesticide is based on function/benefits (25.8%), following other farmers who already use a similar brand (s5.8 percent, price of pesticide (17.2%). SEM test results show quality results product, place, and promotion do not have a direct influence on purchasing decisions, only price has a direct influence on pesticide purchasing decisions. In testing the relationship with brand image, product quality and promotion have a significant positive influence, while price and place have a significant negative influence. Further findings found that brand image succeeded in mediating price, place, promotion with pesticide purchasing decisions, but brand image failed to mediate product quality with purchasing decisions. Furthermore, brand image had a significant positive influence on pesticide purchasing decisions.